Prevalence of glucose-6-phosphate dehydrogenase deficiency and the potential of neonatal complication prevention - Manar Al-Lawama; Nour Ghanem; Esraa Arabiat; Dina Abu-Assab; Aseel Dmour; Salam Al-Kayed; Arwa Kiswani; Hadeel Al-Zoubi; Eman Badran; Abdulilah AlTayar; Aaya Alnajar; Asma Altayar; et al. (Hygeia Press di Corridori Marinella, 2022)
Background: Glucose-6-phosphate dehydrogenase (G6PD) deficiency is a common inherited disease. The aim of our study was to assess the prevalence and gender distribution of G6PD deficiency in Jordan and to establish the rate of neonatal morbidity in G6PD-deficient patients compared to healthy neonates. Moreover, the present study aimed to evaluate the neonatal G6PD deficiency screening program. Materials and methods: This was a retrospective study conducted at a tertiary hospital in Amman, Jordan. All infants born between January 2016 and March 2020 were included. Demographic and clinical data were extracted from the patients' medical records and hospital laboratory databases. Results: During the study period, 11,128 neonates underwent the neonatal screening program, and 114 (1.02%) did not undergo screening at the appropriate time. Among the included neonates, the overall prevalence of G6PD deficiency in our population was 1.44%, with a higher proportion among males than among females (2.38% vs. 0.36%), with a male-to-female ratio of 7:1. The rate of pathological neonatal hyperbilirubinemia and blood exchange transfusion was significantly higher in patients with G6PD deficiency.  Conclusions: The evidence from this study suggests that our institution's G6PD screening program is a successful program. G6PD deficiency is prevalent among Jordanian males. It is a major cause of pathological neonatal hyperbilirubinemia and blood exchange transfusion.